Information Security Theory and Practice: 12th IFIP WG 11.2 International Conference, WISTP 2018, Brussels, Belgium, December 10-11, 2018, Revised Selected Papers - Blazy, Olivier; Yeun, Chan Yeob (Lecture Notes in Computer Science, 2019)
This volume constitutes the refereed proceedings of the 12th IFIP WG 11.2 International Conference on Information Security Theory and Practices, WISTP 2018, held in Brussels, Belgium, in December 2018.The 13 revised full papers and 2 short papers presented were carefully reviewed and selected from 45 submissions. The papers are organized in the following topical sections: real world; cryptography; artificial learning; cybersecurity; and Internet of things.